Even a low-dose of moderate-to-vigorous physical activity reduces mortality by 22% in adults aged ≥60 years: a systematic review and meta-analysis. Issue 19 (3rd August 2015) - Hupin, David; Roche, Frédéric; Gremeaux, Vincent; Chatard, Jean-Claude; Oriol, Mathieu; Gaspoz, Jean-Michel; Barthélémy, Jean-Claude; Edouard, Pascal
Abstract : Background: The health benefits of 150 min a week of moderate-to-vigorous-intensity physical activity (MVPA) in older adults, as currently recommended, are well established, but the suggested dose in older adults is often not reached. Objectives: We aimed to determine whether a lower dose of MVPA was effective in reducing mortality, in participants older than 60 years. Methods: The PubMed and Embase databases were searched from inception to February 2015. Only prospective cohorts were included. Risk ratios of death were established into four doses based on weekly Metabolic Equivalent of Task (MET)-minutes, defined as inactive (reference), low (1–499), medium (500–999) or high (≥1000). Data were pooled and analysed through a random effects model using comprehensive meta-analysis software. Results: Of the 835 reports screened, nine cohort studies remained, totalling 122 417 participants, with a mean follow-up of 9.8±2.7 years and 18 122 reported deaths (14.8%). A low dose of MVPA resulted in a 22% reduction in mortality risk (RR=0.78 (95% CI 0.71 to 0.87) p<0.0001). MVPA beyond this threshold brought further benefits, reaching a 28% reduction in all-cause mortality in older adults who followed the current recommendations (RR=0.72 (95% CI 0.65 to 0.80) p<0.0001) and a 35% reduction beyond 1000 MET-min per week (RR=0.65 (95% CI 0.61 to 0.70) p<0.0001). Conclusions: A dose of MVPA below current recommendations reduced mortality by 22% in older adults. A further increase in physical activity dose improved these benefits in a linear fashion. Older adults should be encouraged to include even low doses of MVPA in their daily lives.